Analysis of The Role of YouTube in Increasing Interest in Reading Indonesian Literature in Grade VII Students of Junior High School - Fadliah Ilmah; Hasnur Ruslan; Ade Nurul Izatti; Juniati; Nirmayanti (Universitas Islam Negeri Palopo, 2025)
This study aims to describe the role of YouTube in increasing interest in reading Indonesian literature in Grade VII students of SMP Negeri 17 Palu. The types of research used are qualitative research and descriptive research. The method used in this study is a qualitative method. The data collection techniques used in this study are: 1) Observation, 2) Interview, 3) Documentation. The technical data analysis in this study is data reduction, data presentation, and conclusion drawn. The results of this study show that YouTube plays a significant role in increasing students' interest in reading literature. Through video shows such as poetry readings, short film adaptations of short stories, and explanations of literary intrinsic elements, students become more enthusiastic, actively discuss, and able to understand the content of literary works more easily. YouTube also helps increase students' intrinsic motivation, foster appreciative attitudes, and encourage them to read literary texts independently. Teachers use YouTube not only as a medium for video playback, but also as a means of reflection, discussion, and understanding strengthening. Supporting factors in the use of YouTube include the availability of internet access, students' enthusiasm for digital media, and the abundance of quality literary content. The obstacles found are network limitations, potential distractions for entertainment content, and limited learning time in the classroom. Overall, this study concludes that YouTube is an effective and relevant learning medium to increase interest in reading Indonesian literature among junior high school students.